Phosphatidylinositol 4, 5‐bisphosphate‐specific phospholipase C β1 selectively binds dipalmitoyl and distearoyl phosphatidic acids via Lys946 and Lys951. Issue 6 (2nd September 2022) - Hoshino, Fumi; Nakayama, Maika; Furuta, Masataka; Murakami, Chiaki; Kato, Ayumu; Sakane, Fumio
Abstract: Phospholipase C (PLC) β1 hydrolyzes 1‐stearoyl‐2‐arachidonoyl (18:0/20:4)‐phosphatidylinositol (PtdIns) 4, 5‐bisphosphate to produce diacylglycerol, which is converted to phosphatidic acid (PtdOH), in the PtdIns cycle and plays pivotal roles in intracellular signal transduction. The present study identified PLCβ1 as a PtdOH‐binding protein using PtdOH‐containing liposomes. Moreover, the comparison of the binding of PLCβ1 to various PtdOH species, including 14:0/14:0‐PtdOH, 16:0/16:0‐PtdOH, 16:0/18:1‐PtdOH, 18:0/18:1‐PtdOH, 18:0/18:0‐PtdOH, 18:1/18:1‐PtdOH, 18:0/20:4‐PtdOH, and 18:0/22:6‐PtdOH, indicated that the interaction of PLCβ1 with 16:0/16:0‐PtdOH was the strongest. The PLCβ1‐binding activity of 18:0/18:0‐PtdOH was almost the same as the binding activity of 16:0/16:0‐PtdOH. Furthermore, the binding of PLCβ1 to 16:0/16:0‐PtdOH was substantially stronger than 16:0/16:0‐phosphatidylserine, 16:0/16:0/16:0/16:0‐cardiolipin, 16:0/16:0‐PtdIns, and 18:0/20:4‐PtdIns. We revealed that a PLCβ1 mutant whose Lys946 and Lys951 residues were replaced with Glu (PLCβ1‐KE) did not interact with 16:0/16:0‐PtdOH and failed to localize to the plasma membrane in Neuro‐2a cells. Retinoic acid‐dependent increase in neurite length and numbers was significantly inhibited in PLCβ1‐expressing cells; however, this considerable attenuation was not detected in the cells expressing PLCβ1‐KE. Overall, these results strongly suggest that PtdOHs containing only saturated fatty acids, including 16:0/16:0‐PtdOH, which are not derived from the PtdIns cycle, selectively bind to PLCβ1 and regulate its function.